Mechanisms and potential therapeutic targets of SphK1 and SphK2 in hepatocellular carcinoma - Xu, XiaoYing; Li, HengFei; Li, RuiSi; Xu, Yue; Xu, YiHeng; Huang, HaiTang; Lv, XiaoJuan; Liao, Chu; Ye, JunQiu; Bo, Liu (Frontiers in Medicine, 2025)
Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related deaths globally. Sphingosine-1-phosphate (S1P) is catalyzed by sphingosine kinases SphK1 and SphK2 and plays a key role in HCC progression: SphK1 can drive tumor proliferation, migration, and angiogenesis. It activates the PI3K/AKT/mTOR and MAPK/ERK signaling pathways and mediates chemoresistance and immune suppression; SphK2 enhances histone acetylation and upregulates pro-oncogene expression through nuclear S1P. It also maintains telomere activity via mitochondrial S1P, which promotes tumor survival and facilitates resistance to regorafenib. In targeted therapy, SphK1 inhibitors (e.g., PF-543) and SphK2 inhibitors (e.g., ABC294640) have shown significant anti-tumor effects in preclinical models. Future research should focus on elucidating the regulatory networks of SphK1/SphK2 in different HCC subtypes, developing highly selective inhibitors, and advancing clinical trials based on metabolic-immune interaction regulation. This paper systematically summarizes the mechanisms of action and therapeutic progress of SphK1/SphK2 in HCC. It provides an important theoretical basis for the clinical translation of precision therapy strategies in HCC.